O desenvolvimento de competências profissionais: um levantamento com os egressos de um curso de mestrado profissional do campo de públicas - Avaristo, João Augusto de Campos (2019)
This research aims to map the main competences developed by the graduates of the Professional Master’s degrees in Management of Organizations and Public Systems, of the Federal University of São Carlos (UFSCar), as a consequence of the accomplishment of the said course. For this, a historical contextualization of the people management as field of study is made; presenting crucial concepts of the evolution of people management, such as strategic management and competency-based management, the historical evolution of labor relations in the public service since from the Vargas Government, up to Lula/Dilma Governments. It’s also made a portrait of the identifiable competencies in professionals of the public services; besides of contextualize, seeking to understand the post-graduation in Brazil, until the Professional Master’s Degree. It is about a quantitative research, applied, descriptive and exploratory, whose adopted method for the data to collect is the survey, through a cross-sectional study, of structured questionnaires on a Likert scale. The results are analyzed and discussed based on tables, graphics, dispersion measures and other methods, that allow us to trace the graduates profile of the course, enabling the comparison between the data collected in this research and the data presented by Capes; in this way, we can define that the profile of the ex-students indicates a population that is essentially feminine, working in the Federal public service, with age between 35 and 39 years old. Regarding competencies, with the help of an indicator called a standard score, a ranking of the competencies explored in this study was elaborated, identifying which one had higher and lower development indices, for the graduates, as a result of the post-graduation; after such ranking, competences were grouped into three categories: high, medium, low and very low degree of development, according to the definition of the median and quartiles of the data obtained. Thus, this research aims to foster discussions in the field of competence-based management in the public service, to build subsidies for self-reflection in postgraduate programs, as well as to support other researchers, contributing to effective and efficient people management within the public administration.